Pelatihan Eco-Enzyme Sebagai Upaya Pengelolaan Sampah Rumah Tangga - Dyah Ayu Sri Hartanti; Ulfa Wulan Agustina; Laili Nur Afifah; Dwi Santika; Alfiyan Taufiqur Rohman (Media Abdimas, 2023)
This training introduced the manufacture of Eco-Enzyme innovations inhousehold organic waste processing in reducing environmental pollution. Thetarget for the Eco-Enzyme manufacturing training activity was a general publicgroup, namely PKK mothers in Sudimoro Village, Megaluh District, JombangRegency, who were attended by as many as PKK mothers. The 20 participants inthis activity were held at the Sudimoro Village Hall. The steps taken in this activityinclude socialization, training, monitoring, and evaluation. In carrying out theactivities of KKN Sudimoro Megaluh members, activities are carried out in theform of socialization, training, and face-to-face mentoring. The economic impactof the Eco-Enzyme manufacturing training is that it can produce Eco-Enzymeproducts which have the potential to become marketable products and canincrease the income of the people of Sudimoro Village. The social impact of theEco-Enzyme manufacturing training is that it can create an Eco-Enzymeproduction business so that later it can create jobs for the surroundingcommunity, especially the residents of Sudimoro Village. reduce the amount ofhousehold organic waste that can interfere with the comfort and beauty of theSudimoro Village environment. The health impact of Eco-Enzyme manufacturingtraining is that it can create clean and healthy environmental conditions.